Fat metabolism during exercise: a review. Part I: fatty acid mobilization and muscle metabolism - Jeukendrup, A. E.; Saris, W. H.; Wagenmakers, A. J. (International Journal of Sports Medicine, 1998)
This is the first part in a series of three articles about fat metabolism during exercise. In this part the mobilization of fatty acids and their metabolism will be discussed as well as the possible limiting steps of fat oxidation. It is known for a long time that fatty acids are an important fuel for contracting muscle. After lipolysis, fatty acids from adipose tissue have to be transported through the blood to the muscle. Fatty acids derived from circulating TG may also be used as a fuel but are believed to be less important during exercise. In the muscle the IMTG stores may also provide fatty acids for oxidation after stimulation of hormone sensitive lipase. In the muscle cell, fatty acids will be transported by carrier proteins (FABP), and after activation, fatty acyl CoA have to cross the mitochondrial membrane through the carnitine palmytoyl transferase system, after which the acyl CoA will be degraded to acetyl CoA for oxidation. The two steps that are most likely to limit fat oxidation are fatty acid mobilization from adipose tissue and transport of fatty acids into the mitochondria along with mitochondrial density and the muscles capacity to oxidize fatty acids.